Atos de improbidade administrativa no Marco Regulatório das Organizações da Sociedade Civil - Vitor, Viviane Formigosa (2019)
Federal Legislative Act no. 13.019/2014, also known as the Third Sector Act, was enacted to provide enforcement against new types of administrative improbity according to the new conduct descriptions introduced by this Act into articles 10 and 11 of the Administrative Improbity Act enacted by Federal Legislative Act no. 8.249/1992. This research focuses on studying those new conducts now deemed as improbity acts, but first understanding the nature of acts of fomenting before the enactment of Act no. 13.019/2014. Then, the main legal aspects of the new Act be tackling the innovations enforced to voluntary partnerships between the Public and Third Sector entities. After that, the new accountability system enforced against Third Sector entities will be analyzed in the constitutional administrative improbity regime so that final conclusions regarding the legal aspects of the new conducts and applicable sanctions can be presented